Psychosocial Adaptation in Lung Cancer Patients: a Literature Review - Syamsiar, Pradika Ghozi; Rondhianto, Rondhianto; Wijaya, Dodi (Universitas Malahayati, 2024)
ABSTRACT Lung cancer is one type of cancer with the highest mortality rate, this is often due to delays in diagnosis and the impact of prognosis which can affect the psychosocial adaptation of lung cancer patients. Analyze psychosocial adaptation problems in lung cancer patients, their impacts, and treatment strategies. Systematic review used the PRISMA protocol and JBI scoring tool to determine eligible articles. Five electronic databases were used (Pubmed; Science Direct and Google Scholar. Inclusion criteria included research on lung cancer published in English in the last ten years (2014-2024). The results showed that 20 articles met the inclusion criteria. The results of the review show several common problems experienced by lung cancer patients, including depression, anxiety, social isolation, stigmatization, mental health problems, and difficulties in adaptation. The impact is a decrease in emotional well-being, a reduction in quality of life, an increase in physical symptoms, and a worsening of the disease prognosis. Several prevention strategies include providing multidisciplinary therapy through supportive and palliative care, improving the quality of psychosocial health services, cognitive behavioral therapy, social support therapy, psycho-education, increasing social support, spiritual treatment, increasing healthy behavior, and using confrontation and stress coping. Psychosocial problems experienced by lung cancer patients are often complex and can include various aspects. Several common issues experienced by lung cancer patients are related to psychosocial problems. The impact of psychosocial problems can worsen the prognosis of lung cancer so several treatment efforts are needed to overcome psychosocial problems in lung cancer patients. Keywords: Adaptation, Lung Cancer, Literature Review, Psychosocial